Engaging with peers, mentors and native speakers as language learning partners in an online environment - Jessica Chakowa (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication, 2019)
Opportunities to interact in the target language have a major impact on language learning and motivation. This paper is based on empirical research conducted at an Australian university. It identifies factors that encourage beginner learners of French to participate in asynchronous online interactions with learning partners of different language proficiency levels: peers, mentors and native speakers. It then highlights the benefits of providing opportunities to engage with multiple partners in accordance with students' attitudes and preferences, which fluctuate over time. This progressive approach takes form in encouraging students to contribute to a shared knowledge and improve their productions, it enables them to experience comfort and authenticity, and ultimately, prepare for real-life situations. This study demonstrates that the exposure to the three groups of learning partners as a whole worth more than their mere juxtaposition.